Growth Pattern and Copper Accumulation in Callus of Datura metel - Yulita Nurchayati; Santosa Santosa; Laurentius Hartanto Nugroho; Ari Indrianto (Biosaintifika: Journal of Biology & Biology Education, 2016)
This experiment was aimed to evaluate the copper accumulation using callus culture of Datura metel L. The culture was established from leaves onto MS contained NAA 2.5 mg/L and Kinetin 0.5 mg/L as the control. The exposure of the culture was carried out by 2 copper compounds as treatment, i.e. CuCl2.2H2O and Na2CuEDTA at level concentration 0.; 0.1; 5; 10; 15; and 20 µM. The growth pattern of callus in control showed increasing growth rate in 36 days, whereas exponential stage was reached at 12-20th doi*. Whilst, after 10 doi, the treatment showed constant growth pattern. The absorption rate of the culture was increased by the addition of the CuCl2.2H2O at 5 – 15 µM of level concentration but declined at 20µM. The maximum rate of accumulation of Cu (0,1519 mg g-1) was obtained at 15 µM. Instead, the addition of Na2CuEDTA at 5 – 20µM of level concentration showed the significant increment while the maximum accumulation was obtained at 20µM (0,1420 mg g-1). The existence of chelator in copper compound reduced the rate of toxicity while all tolerance index values were between 66,24 and 97,28 %.The results suggested the role of callus of D. metel as  that fairly absorbed and accumulated Cu2+. Exposure with CuCl2.2H2O indicated higher accumulation than Na2CuEDTA.How to CiteNurchayati, Y., Santosa, S., Nugroho, L. H., Indrianto, A. (2016). Growth Pattern and Copper Accumulation in Callus of Datura metel. Biosaintifika: Journal of Biology Biology Education, 8(2), 135-140.